2012
DOI: 10.1111/j.1600-6143.2011.03842.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-Specific Regulatory and Effector T Cells Share TCR Clonality—Possible Relation to Repetitive CMV Infections

Abstract: Cytomegalovirus (CMV) infections have a major impact on morbidity and mortality of transplant patients. Among the complex antiviral T-cell response, CMV-IE-1 antigen-specific CD8+ cells are crucial for preventing CMV disease but do not protect from recurring/lasting CMV reactivation. Recently, we confirmed that adoptive transfer of autologous IE-1/pp65-specific T-cell lines was able to combat severe CMV disease; however, the control of CMV infection was only temporary. We hypothesized that CMV-induced regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…However, the detection of this cytokine in combination with both TGF-␤1 and permanent FoxP3 expression is usually associated with regulatory functions (2,52). Most importantly, L-Tag-induced CD4 ϩ CD25 ϩ(high) FoxP3 ϩ CD103 ϩ T cells also display a remarkable capacity to inhibit the proliferation of autologous anti-CD3/CD28-stimulated CD4 ϩ CD25 Ϫ lymphocytes compared to HCMVpp65-stimulated CD4 ϩ CD25 ϩ(high) FoxP3 ϩ CD103 ϩ/Ϫ T cells, in accordance with recently published reports (46,56). Collectively, these data hint at mechanisms potentially underlying our findings in ex vivo-activated PBMC.…”
Section: Discussionsupporting
confidence: 74%
“…However, the detection of this cytokine in combination with both TGF-␤1 and permanent FoxP3 expression is usually associated with regulatory functions (2,52). Most importantly, L-Tag-induced CD4 ϩ CD25 ϩ(high) FoxP3 ϩ CD103 ϩ T cells also display a remarkable capacity to inhibit the proliferation of autologous anti-CD3/CD28-stimulated CD4 ϩ CD25 Ϫ lymphocytes compared to HCMVpp65-stimulated CD4 ϩ CD25 ϩ(high) FoxP3 ϩ CD103 ϩ/Ϫ T cells, in accordance with recently published reports (46,56). Collectively, these data hint at mechanisms potentially underlying our findings in ex vivo-activated PBMC.…”
Section: Discussionsupporting
confidence: 74%
“…We have previously shown that CD4 ϩ T cells specific to HCMV ORF-encoded proteins UL138 and LUNA have the capacity to secrete the immunomodulatory cytokine IL-10, as well as have distinct UL138-and LUNAspecific CD4 ϩ T cell populations able to secrete IFN-␥, a Th1-defined cytokine (47). Others have identified CMV-specific CD4 ϩ T cells which secrete IL-10, and their experiments suggested that the generation of inducible T regulatory (iTreg) cells specific for HCMV (pp65 and IE ORFs) was related to frequent exposure to the CMV antigen (49). This suggests that an older CMV-seropositive donor may have increased numbers of CD4 ϩ T cells secreting IL-10 following CMV stimulation because the individual was potentially exposed to viral antigens for a longer period of time.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously identified populations of CD4 ϩ T cells specific for the HCMV proteins UL138 and LUNA, which secrete IL-10 (47). Others have observed secretion of IL-10 by CMV-specific CD4 ϩ T cells in response to stimulation by pp65 and IE1, and they demonstrated that frequent exposure to CMV antigens drove the generation of an iTreg CD4 ϩ T cell population specific to HCMV (49). We hypothesized that older CMV-seropositive donors may have increased numbers of CD4 ϩ T cells secreting IL-10 following CMV antigen stimulation due to longer periods of exposure to viral antigens and that this subset of CMV-specific CD4 ϩ T cells may inhibit efficient recognition of the virus by IFN-␥-secreting CMV-specific CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar experiments with expanded CD4 + CD25 + CD134 + CD39 + T-cell lines found approximately 20% of cells secreted IFN-γ, this may be partly due to the expansion of memory non-Treg cells (15−20%) within the Ag-specific CD4 + CD25 + CD134 + CD39 + T-cell line. Alternatively, it has also been reported that induced CD39 + Helios − IL-2 low FOXP3 + pTreg cells can produce IFN-γ [35].…”
Section: Discussionmentioning
confidence: 99%